Utilization of Fermented Cacao Rind Flour (Theobroma cacao) Used Cattle’s Rumen Fluid in Artificial Feed to The Growth of Tilapia Fingerlings (Oreochromisniloticus) - Sunarto Sunarto; Indra Suharman; Adelina Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research has been implemented in April-May 2019 at Fish Nutrition Laboratory, Fisheries and Marine science Faculty, the University of Riau. The purpose of this research was to determine the best percentage fermented cacao rind flour (FCRF) in artificial feed to increase the growth of tilapia fingerlings. The research method use in this study was an experimented method and completely randomized design with five treatments and three replication. The treatment study were P0 (FCRF 0% + Soy Flour (SF) 100%), P1 (FCRF 30% + SF 70%), P2 (FCRF 40% + SF 60%), P3 (FCRF 50% + SF 50%), P4 (FCRF 60% + SF 40%). The best results were treatment of fermented cacao rind flour with a percentage of 50% at P3 with a absolute weight growth of 14,21 g, specific growth rate of 7,30%, 95% survival rate and feed efficiency with a value of 96,87%. The range of quality of the water at all of temperature treatmentrange between 28-31oC, pH 5-6, and oxygen concentration 5-5,9 mg/L. Keywords:Fermented, cacao rind flour, cattle’s rumen fluid, Oreochromisniloticus.